SUSTAINABILITY ASSESSMENT OF COASTAL ZONE - A PILOT IN PHU CAT DISTRICT, BINH DINH PROVINCE - Tinh, Vo Thanh; Ly, Che Dinh; Thanh, Luong van (Vietnam Journal of Marine Science and Technology, 2014)
Based on the sustainability assessment indicators conducted previously, the authors studied and built the sustainable indicators for the factors involved in the assessment with 6 themes and 38 indicators as well as sustainable levels (5 levels) in order to assess the sustainable conditions in coastal zone at the  pilot site in Phu Cat district. The authors also proposed to apply the method of analysis hierarchy process (AHP) to establish a set of weights for each subject and indicator. After calculating the assessment results for each indicator through the method of fuzzy comprehensive evaluation (FCE) by the membership functions, the overall evaluation results for the entire Phu Cat district were done. Through the implementation of these methods the evaluation results showed that the sustainability of Phu Cat district is at average level.